Performance and egg quality traits of egg-type chickens fed cottonseed cake based diets (2015)
The study evaluated the performance of egg type chickens fed diets where Cottonseed cake (CSC) replaced Soybean cake (SBC) in five experimental rations such that 0% (control), 15%, 30%, 45% and 60% of CSC replaced SBC. The design of the experiment was completely randomized design (CRD). Chemical analysis was carried out to determine the crude protein (CP) and gossypol contents of CSC. Seventy-five 23 week - old egg type chicken were fed with experimental layer diets for 12 weeks. Parameters evaluated include hen-day production (HDP), Feed conversion ratio (FCR), egg weight (EW) and haugh units (HU). All data were analyzed using descriptive statistics and analysis of variance. The determined CP of CSC was 35.11% and its gossypol content was 570g/ton. FCR ranged from 1.6 to 4.9, HDP from 47% to 68%, EW from 47.5 to 62.8 g, and HU from 3.1 to 6.7. Chickens on 60% CSC replacement for SBC had higher values for the parameters measured which were not significantly different from the control. CSC can replace up to 60% SBC without adverse effects on performance and egg quality characteristics of egg type birds.